X-(-2x+13)=2

Simple and best practice solution for X-(-2x+13)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-(-2x+13)=2 equation:


Simplifying
X + -1(-2x + 13) = 2

Reorder the terms:
X + -1(13 + -2x) = 2
X + (13 * -1 + -2x * -1) = 2
X + (-13 + 2x) = 2

Reorder the terms:
-13 + X + 2x = 2

Solving
-13 + X + 2x = 2

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + X + 13 + 2x = 2 + 13

Reorder the terms:
-13 + 13 + X + 2x = 2 + 13

Combine like terms: -13 + 13 = 0
0 + X + 2x = 2 + 13
X + 2x = 2 + 13

Combine like terms: 2 + 13 = 15
X + 2x = 15

Add '-2x' to each side of the equation.
X + 2x + -2x = 15 + -2x

Combine like terms: 2x + -2x = 0
X + 0 = 15 + -2x
X = 15 + -2x

Simplifying
X = 15 + -2x

See similar equations:

| -3-7b=-7b-6 | | 5a-8=5 | | 8n^2-18=4n | | -2-p=15 | | -6(3h+9)=-22 | | Y/4-7=-3 | | X-3/2=4/8 | | 3(4n+7)=-32 | | 20-n=37 | | 4x1/2=8 | | 60b^2+31b-3=0 | | x^2-34x-273=0 | | 4.75x+2y=3.45 | | -10-a=-15 | | (3+i)(-4+3i)= | | -10-a=15 | | 5a-6-2a=1/ | | P/3-7=14 | | x^2-32x-273=0 | | -k/4-3=10 | | 4a=3.2 | | 6x+4(-3+1x)=13 | | -12=-4/5x | | 6a=6.6 | | 5p+6=4-8 | | 2y=2.2 | | -8+12=2x+11 | | y^2-34y-273=0 | | 2x^3-10x-1=0 | | X+28+(6x+5)+39=180 | | 17x^3-10x-1=0 | | G*2=30-7g |

Equations solver categories